Studi Kritis: Pembelajaran Toleransi dalam Buku Ajar Pendidikan Agama Islam dan Budi Pekerti Sekolah Dasar - Asrianti, Putri Utami; Supriadi, Udin; Anwar, Saepul (BRILIANT: Jurnal Riset dan Konseptual, 2024)
Islamic Religious Education and Ethics textbooks, hereafter written as PAI and BP, are vital elements in instilling character values, including tolerance in schools. However, cases of intolerance still occur frequently in Indonesia and this is often associated with religious education in schools. This research seeks to reveal the proportion of PAI learning materials and how the learning content of tolerance in PAI and BP textbooks. This research uses a qualitative approach with a literature study method that analyzes the content of PAI and BP textbooks published by the Ministry of Education and Culture 2013 Revised Curriculum 2013 (Grades II, III, V, and VI) and Independent Curriculum (Grades I and IV). Data analysis techniques in this study are 3 stages, namely data reduction, data display, and data verification. The results showed that the proportion of material in PAI and BP textbooks is dominated by moral material that is in line with the objectives of Islamic religious education, then in the textbook there are 4 categories of tolerance, namely: (1) tolerance in belief and worship; (2) tolerance of coexistence with other religions; (3) tolerance in inter-community relations; (4) internal tolerance of Muslims packaged with interesting illustrations, especially in independent curriculum books.